Effect of the NMDA receptor partial agonist, d-cycloserine, on emotional processing and autobiographical memory - Chen, R; Capitão, LP; Cowen, PJ; Harmer, CJ (Cambridge University Press, 2020)
Background Studies suggest that d-cycloserine (DCS) may have antidepressant potential through its interaction with the glycine site of the N-methyl-D-aspartate receptor; however, clinical evidence of DCS's efficacy as a treatment for depression is limited. Other evidence suggests that DCS affects emotional learning which may also be relevant for the treatment of depression and anxiety. The aim of the present investigation was to assess the effect of DCS on emotional processing in healthy volunteers and to further characterise its effects on emotional and autobiographical memory.